Reaksi Pasar Modal Indonesia Terhadap Peristiwa Penguman PSBB DKI Jakarta - wahyu irawan; James Andrew Hadiprajitno; H Hersugondo (STEKOM PRESS, 2021)
This research was conducted to see whether there was an abnormal return before and after the Jakarta PSBB announcement. The sample was selected using a purposive sampling technique from 30 stocks that are members of the Jakarta Islamic Index (JII) in the 2020 period. The data in this study used secondary data, opening, and closing prices, and Composite Stock Price Index (IHSG). This research is an event study using an event study with an observation period of eight days, four days before the announcement and after the day after the announcement of the Jakarta PSBB. Hypothesis testing uses the Wilcoxon signed ranking test. Based on the research results, there was no change in abnormal return before and after the announcement of the Jakarta PSBB announcement